Sphere: Multi-Touch Interactions on a Spherical Display - Benko, Hrvoje; Wilson, Andy; Balakrishnan, Ravin (UIST '08 Proceedings of the 21st annual ACM symposium on User interface software and technology, 2008)
Sphere is a multi-user, multi-touch-sensitive spherical display in which an infrared camera used for touch sensing shares the same optical path with the projector used for the display. This novel configuration permits: (1) the enclosure of both the projection and the sensing mechanism in the base of the device, and (2) easy 360-degree access for multiple users, with a high degree of interactivity without shadowing or occlusion. In addition to the hardware and software solution, we present a set of multi-touch interaction techniques and interface concepts that facilitate collaborative interactions around Sphere. We designed four spherical application concepts and report on several important observations of collaborative activity from our initial Sphere installation in three high-traffic locations.